Development of Antifungal Peptides against Cryptococcus neoformans; Leveraging Knowledge about the cdc50Δ Mutant Susceptibility for Lead Compound Development - Robert J. Tancer (Microbiology Spectrum, 2022)
ABSTRACT Cryptococcus neoformans is a major fungal pathogen that often causes life-threatening meningitis in immunocompromised populations. This yeast pathogen is highly resistant to the echinocandin drug caspofungin. Previous studies showed that Cryptococcus lipid translocase (flippase) is required for the caspofungin resistance of that fungus. Mutants with a deleted subunit of lipid flippase, Cdc50, showed increased sensitivity to caspofungin. Here we designed an antifungal peptide targeting the P4-ATPase function. We synthesized stable peptides based on the Cdc50 loop region to identify peptides that can sensitize caspofungin by blocking flippase function and found that myristylated peptides based on the “AS15 sequence” was effective at high concentrations. A modified peptide, “AW9-Ma” showed a MIC of 64 μg/mL against H99 wild type and a fractional inhibitory concentration (FIC) index value of 0.5 when used in combination with caspofungin. Most notably, in the presence of the AW9-Ma peptide, C. neoformans wild type was highly sensitive to caspofungin with a MIC of 4 μg/mL, the same as the cdc50Δ mutant. Further assays with flow cytometry showed inhibition of the lipid flippase enzyme activity and significant accumulation of phosphatidylserine on the cell membrane surface. Using a fluorescently labeled peptide, we confirmed that the peptide co-localized with mCherry-tagged P4-ATPase protein Apt1 in C. neoformans. Structure-activity relationship studies of the AW9 sequence showed that two lysine residues on the peptide are likely responsible for the interaction with the P4-ATPase, hence critical for its antifungal activity. IMPORTANCE The authors have developed a lead compound peptide antifungal drug targeting a protein from the organism Cryptococcus neoformans. Binding of the drug to the target fungal protein causes charged lipid molecules to be retained on the surface. This peptide works in synergy with the existing antifungal drug caspofungin. Echinocandin drugs like caspofungin are one of the few classes of existing antifungals. Due to the high concentrations needed, caspofungin is rarely used to treat C. neoformans infections. The authors believe that their new compound provides a way to lower the concentration of caspofungin needed to treat such infections, thus opening the possibility for greater utility of these antifungal.